Enhanced hypocrellin production via coexpression of alpha-amylase and hemoglobin genes in Shiraia bambusicola - Ruijie Gao; Huaxiang Deng; Zhengbing Guan; Xiangru Liao; Yujie Cai (AMB Express, 2018)
Abstract Shiraia bambusicola is an important and valuable macrofungus and hypocrellins are its main secondary metabolites which have been widely applied in many medical fields. However, during SSF process of this filamentous fungus, use ratio of corn substrate and dissolved oxygen supply are two main limiting factors, which influence production cost, yield and product quality. To solve these problems, overexpressions of amy365-1 and vgb in S. bambusicola were investigated and three overexpression transformants were constructed. Results demonstrated that expressions and coexpression of AMY365-1 and VHb not only increased the productions of biomass, amylase, hypocrellin, but also up-regulated relative expression levels of four central carbon metabolism genes (pdc, ald, acs, acc) and seven hypocrellin biosynthesis genes (fad, mono, zftf, omef, msf, pks, mco). Furthermore, expression of VHb decreased SSF period. When amy365-1 and vgb were coexpressed, relative expression levels of zftf and pks reached their highest levels at 72 h under liquid fermentation, hypocrellin production reached the highest level 75.85 mg/gds which was 2.99-fold compared with wild type strain within 11 days under SSF, and residual starch of solid substrates was decreased from 35.47 to 14.57%.